Persepsi Guru Terhadap Karakter Anak Hiperaktif di SDN Benua Anyar 4 Banjarmasin - Abidinsyah Abidinsyah (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
Education is considered as an aspect that has an important role in shaping the nation's generation so that students do not lose their grip on traditions and cultural paths in accordance with the philosophy of the Indonesian nation. The implementation of the 2013 curriculum in education emphasizes character education. Teachers certainly have difficulty in internalizing character values in hyperactive children, considering that not all characters can be internalized to students. In this case, teachers have a perception in internalizing character values in hyperactive children. This study aims to describe the perception of teachers towards the character of hyperactive children in generalizing character values and constraints in the realization of character values at SDN Benua Anyar 4 Banjarmasin. This type of research is qualitative descriptive research. The subjects of the study were class teachers and assisted teachers in grade II grade IV sdn Banua Anyar 4 Banjarmasin. Data collection techniques are conducted through observation and interview. Data analysis techniques are performed by data collection, data grouping, and data inferferring. The results of the study were obtained as follows: (1) Teachers have almost the same perception of the character of hyperactive children, namely hyperactive children are children who have difficulty concentrating, avoid thinking, nosy activities, can not do tasks by themselves, can not be silent, (2) Teachers use the way of internalizing character values in school by applying in each subject and daily behavior, (3) Class teachers experience obstacles in internalizing character values such as constraints from the environment, constraints on teacher's lack of competence to character scores, constraints from students in the school environment and constraints on parents of hyperactive children.